Upgrading car saloon & services for Otobacs Sdn. Bhd. at No. 10 Jalan Dato Seri Ahmad Said, 30450, Ipoh, Perak Darul Ridzuan, Malaysia / Mohammad Imran Johari - Johari, Mohammad Imran (Faculty of Architecture, Planning and Surveying, 2011)
A final year student pursuing a diploma course in Interior Design is required to prepare a final year project. All the design must be related to the choosen project. Before begin with design , every related aspect must be considered and identified. Therefore we must do a research, case study, design schematic and the planning to make sure that the client will give the good feedback with our design. In addition, systematic work must been done properly start from the design development until the end of the project. Upgrading car saloon & services is one of the potential business for my client to expand their business. It is because car saloon & services is a growing business in Malaysia. They also want to attract the people come to their shop. Regarding to the issues, the space planning has come out with design concept and the images. The planning that have been created and the idea that we want to implement into the space must be related to the concept and images. With the concept ’’From parts to arts” and the ultra modern images will implement to the space and the building that have been analysis will be used as clients approval. For the conclusion The good design is how we implement the concept and images into the design centre, followed by the development of ideas.